Strengthening the Fund's Ability to Assist Low-Income Countries Meet Balance of Payments Needs Arising from Sudden and Exogenous Shocks. (Policy Papers; Policy Paper ;, 2005)
At the Executive Board discussion on the role of the Fund in low-income countries, Directors requested proposals to address the absence of concessional instruments other than the PRGF in the Fund's financial assistance to low-income members facing exogenous shocks. Against this background, this paper analyses the main issues in designing such a window within the PRGF Trust.